Butyrate prevents valproate‐induced liver injury: In vitro and in vivo evidence. Issue 1 (26th November 2019) - Pirozzi, Claudio; Lama, Adriano; Annunziata, Chiara; Cavaliere, Gina; De Caro, Carmen; Citraro, Rita; Russo, Emilio; Tallarico, Martina; Iannone, Michelangelo; Ferrante, Maria Carmela; Mollica, Maria Pina; Mattace Raso, Giuseppina; et al.
Abstract: Sodium valproate (VPA), an antiepileptic drug, may cause dose‐ and time‐dependent hepatotoxicity. However, its iatrogenic molecular mechanism and the rescue therapy are disregarded. Recently, it has been demonstrated that sodium butyrate (NaB) reduces hepatic steatosis, improving respiratory capacity and mitochondrial dysfunction in obese mice. Here, we investigated the protective effect of NaB in counteracting VPA‐induced hepatotoxicity using in vitro and in vivo models. Human HepG2 cells and primary rat hepatocytes were exposed to high VPA concentration and treated with NaB. Mitochondrial function, lipid metabolism, and oxidative stress were evaluated, using Seahorse analyzer, spectrophotometric, and biochemical determinations. Liver protection by NaB was also evaluated in VPA‐treated epileptic WAG/Rij rats, receiving NaB for 6 months. NaB prevented VPA toxicity, limiting cell oxidative and mitochondrial damage (ROS, malondialdehyde, SOD activity, mitochondrial bioenergetics), and restoring fatty acid oxidation (peroxisome proliferator‐activated receptor α expression and carnitine palmitoyl‐transferase activity) in HepG2 cells, primary hepatocytes, and isolated mitochondria. In vivo, NaB confirmed its activity normalizing hepatic biomarkers, fatty acid metabolism, and reducing inflammation and fibrosis induced by VPA. These data support the protective potential of NaB on VPA‐induced liver injury, indicating it as valid therapeutic approach in counteracting this common side effect due to VPA chronic treatment.